Coral reef communities contain a wide variety of mutualistic associations none more important than the relationship between corals and their symbiotic dinoflagellates of the genus Symbiodinium sp., commonly referred to as zooxanthellae. The function of Zinc (Zn) as cofactor of several enzyme systems such as extracellular carbonic anhydrase (extracellular CA) which catalyzes the interconversion of HCO3- and CO2. Concentrations of dissolved Zn in oligothropic waters are often very low therefore ma - WIDIASTUTI KARIM; RICHARDUS KASWADJI; TRI PRARTONO; LILY MARIA GORETTI PANGGABEAN (HAYATI Journal of Biosciences, 2011)
Coral reef communities contain a wide variety of mutualistic associations none more important than the relationship between corals and their symbiotic dinoflagellates of the genus Symbiodinium sp., commonly referred to as zooxanthellae. The function of Zinc (Zn) as cofactor of several enzyme systems such as extracellular carbonic anhydrase (extracellular CA) which catalyzes the interconversion of HCO3- and CO2. Concentrations of dissolved Zn in oligothropic waters are often very low therefore may limit the growth of zooxanthellae and their ability to fix CO2 from seawater via the carbonic anhydrase. The aim of this research is to investigate the effect of various concentrations of Zn on the growth and extracellular CA activity in zooxanthellae. Cell density was monitored daily by enumeration with hemocytometer-type chamber (0.1 mm). Extracellular CA was measured in homogenized intact whole cell by a pH drift assay. Results revealed that Zn status strongly influences the growth rate and extracelullar CA activity in zooxanthellae. The specific growth rate and cell density increased two-fold whilst extracelullar CA activity increased 10.5 times higher than that in control with increasing concentrations of Zn from 0 to 80 nM, but decreased when Zn was over 80 nM. Under a concentration of 80 nM was not Zn limited culture, consequently the growth rate of zooxanthellae not dependent on CO2 concentration yet offset by extracelullar CA activity.